Impact of Job Loyalty, Management Performance, Rewards and Recognition and Firm Size on Profitability in Supply Chain of Bank: Empirical Study on Islamic Banks in Iraq - ali Husien, Wesam; Mohammed Aziz, Aziz; Abdulkareem Jasim, Ahmed (International Journal of Supply Chain Management, 2019)
The main objective of this study is to examine the impact of job loyalty, management performance, rewards and recognition, and firm size on profitability in supply chain of bank. Islamic banking industry share increasing day by day and this industry growing rapidly. The model of current study developed on the basis of theoretical background. To investigate the hypothesized model of current study quantitative research design was followed. Data were collected through questionnaire and two hundred ninety 290 questionnaires were distributed among employees of Islamic banks in Iraq. To test the proposed hypothesis SPSS version 23 was used to analyze data. The findings revealed that job loyalty, management performance, rewards and recognition, and firm size have significant and positive impact on bank profitability. The values of this paper show that job loyalty, management performance, rewards and recognition, and firm size enhance the bank profitability.